Kingdom of the Netherlands-Aruba : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the 2005 Article IV Consultation on the Kingdom of the Netherlands-Aruba highlights the economic developments and policies. Meeting the challenges of population aging requires policies that create conditions for faster productivity growth. IMF Staff recommended applying the successful model of public-private sector cooperation developed in the tourism industry to promote diversification in other areas, in particular in financial services. Staff urged the authorities to speed up the restructuring of public companies and reinvigorate their efforts to improve statistics.